Production of Herbicide-Sensitive Strain to Prevent Volunteer Rice Infestation Using a CRISPR-Cas9 Cytidine Deaminase Fusion - Komatsu, Akira; Ohtake, Miki; Shimatani, Zenpei; Nishida, Keiji (Frontiers in Plant Science, 2020)
When cultivated rice seed fall into fields, they may overwinter and spontaneously germinate the next spring. Such germinated plants are termed “volunteer rice.” Volunteer grains originating from feed rice varieties may differ in certain traits, such as quality and taste, as compared with those of rice cultivated for human consumption, which may reduce the overall quality of the final harvested grain. Many rice varieties show resistance to benzobicyclon (BBC), a beta-triketone herbicide (bTH) that inhibits 4-hydroxyphenylpyruvate dioxygenase (HPPD). Recently, the rice gene HIS1 (HPPD INHIBITOR SENSITIVE 1) conferring resistance to BBC and other bTHs was identified. In this study, to suppress the occurrence of volunteer rice invasion, we attempted to generate a BBC-sensitive rice strain via the knockout of the HIS1 gene using genome editing techniques. The production of a his1 knockout line was carried out by the start-codon substitution or stop-codon creation using CRISPR-Cas9 cytidine deaminase fusion, which is useful as a novel amino acid sequence is not generated due to the shifting of the reading frame. The mutation frequencies of independent transgenic plants were 3.6%, 13.5%, 13.8%, and 21.2% at four gRNA for start-codon substitution and three stop-codon creations. The his1 knockout lines were conferred with sensitivity to BBC, re-confirming by genome editing that this is indeed the gene responsible for BBC resistance/sensitivity. The his1 knockout lines also exhibited a sensitive phenotype to other bTHs, including sulcotrione, mesotrione, tembotrione, and tefuryltrione, compared with the wild-type variety “Nipponbare”. These results suggest that genome editing technology can efficiently produce herbicide-sensitive rice lines and reduce the occurrence of volunteer rice invasion without concern for the backcross effort or linkage drugs.